PERAN DAKWAH DIGITAL DALAM MENDORONG PERUBAHAN SOSIAL DI KALANGAN GENERASI Z: Analisis Peran Dakwah Digital dalam Mendorong Perubahan Sosial pada Generasi Z - Fikriyah Zahirah Akram, Shafa'; Kemala Rizki, Puti; Khoriyah, Salamahtul; Indah Maulani, Maria; Al-Ghifari, Hasanudin; Priyono, Dheni; Suyani; Widodo, Dody (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In the era of globalization, the internet and social media have become essential spaces for the development of Islamic preaching (dakwah). Digital media now serves as a primary channel for disseminating religious messages due to its rapid, visual, and easily accessible nature. Generation Z, who grew up alongside technology, prefers Islamic content that is brief, creative, and attractively packaged. Consequently, concise, visual, and message-focused digital dakwah proves more effective in reaching this generation. Digital dakwah has been shown to enhance religious understanding, encourage positive behavioral changes, and build religious communities capable of adapting to digital culture. However, several challenges remain, including the spread of content that contradicts Islamic teachings, biased information, and the negative impacts of social media on youth mindsets. Overall, digital dakwah plays a significant role in shaping the religious awareness of Generation Z, especially when supported by strong digital literacy. This study aims to examine how digital dakwah influences the religious understanding and awareness of Generation Z adolescents. Using a qualitative method based on library research, complemented by findings from previous studies on youth religious behavior in digital spaces, the analysis reveals that platforms such as YouTube, Instagram, TikTok, and Spotify are the primary media through which adolescents access Islamic content.